Antioxidant system of soiny mullet (Liza haematocheila) is responsive to dietary poly-β-hydroxybutyrate (PHB) supplementation based on immune-related enzyme activity and de novo transcriptome analysis. Issue 95 (December 2019) - Qiao, Guo; Sun, Qirui; Zhang, Mingming; Xu, Chen; Lv, Tingli; Qi, Zhitao; Yang, Wenping; Li, Qiang
Abstract: As a dietary supplement, poly-β-hydroxybutyrate (PHB) has been reported to positively influence growth, boost the immune system and enhance disease resistance in fish and shellfish. However, the protective mechanism is little known. Thus, the present study was conducted to evaluate the effect of PHB supplementation on immune-related enzyme activity and transcriptome-based gene expression in soiny mullet ( Liza haematocheila ). Results showed that dietary PHB supplementation could increase antioxidant enzyme activity, including total antioxidant capacity, catalase and superoxide dismutase. A total of 7, 082, 094, 175 and 7, 650, 341, 357 raw reads with mean length of 757 bp were obtained from control and PHB (dietary PHB supplementation at 2%) groups, respectively. There were 46, 106 differentially expressed genes (DEGs) between control and PHB groups, including 21, 828 upregulated and 24, 278 downregulated DEGs. All the DEGs were classified into three gene ontology categories, and 312 DEGs related with immune system process and 760 with the response to a stimulus. Additionally, all DEGs were allocated to 261 Kyoto Encyclopedia of Gene and Genome pathways, and major immune-related pathways were detected, including MAPK/PI3K-Akt/TNF/NF-κB/TCR/TLR signaling pathways. Moreover, the regulation of several observed immune-related genes was confirmed by qRT-PCR. Altogether, this study suggests that antioxidant system is more effective for dietary PHB supplementation and lays the foundation for further study on the precise immunostimulatory mechanism of PHB. Hopefully, it provides insights into exploring biomarker for assessment of immunostimulants in fish culture. Highlights: Poly-β-hydroxybutyrate (PHB) increased antioxidant enzyme activity of soiny mullet, including T-AOC, CAT and SOD. A total of 46, 106 differentially expressed genes were identified post PHB supplementation. Immune pathways/genes were identified in the transcriptome of soiny mullet. MAPK/PI3K-Akt/TNF/NF-κB/TCR/TLR signaling pathways were associated with PHB's regulatory effects.